Conspicuous Compassion, Social Media and Identity: a Case Study of @dr.tirta Instagram Account during the Covid-19 Pandemic - Athalea Kwee; Ezmieralda Melissa (ADI Publisher, 2020)
Social media allow individuals to construct ideal online identities and one of the new ways to do this is by showing conspicuous compassion, or the flaunting of good behaviors to others. Drawing on the antecedents of conspicuous compassion, which are Need for Uniqueness (NFU) and Attention to Social Comparison Information (ATSCI), this research investigates how conspicuous compassion is portrayed by an Indonesian influencer, dr. Tirta Mandira Hudhi, in his Instagram posts. This study employs a textual analysis through the prism of semiotics to interpret the images and captions of the Instagram account @dr.tirta from 23 to 30 March 2020. The results show that @dr.tirta portrays conspicuous compassion through his social interactions, involvement in fighting the coronavirus, unique style, and his knowledge in the medical field. Results also indicate that @dr.tirta is highly susceptible to his followers, thus intentionally adjusts his image to meet their expectations.